2015
DOI: 10.1039/c5nr01839k
|View full text |Cite
|
Sign up to set email alerts
|

Protein corona mitigates the cytotoxicity of graphene oxide by reducing its physical interaction with cell membrane

Abstract: Many recent studies have shown that the way nanoparticles interact with cells and biological molecules can vary greatly in the serum-containing or serum-free culture medium. However, the underlying molecular mechanisms of how the so-called "protein corona" formed in serum medium affects nanoparticles' biological responses are still largely unresolved. Thus, it is critical to understand how absorbed proteins on the surfaces of nanoparticles alter their biological effects. In this work, we have demonstrated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
169
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(198 citation statements)
references
References 61 publications
16
169
1
4
Order By: Relevance
“…In our current study, WS 2 nanosheets were probably partially coated with protein FBS in the cell viability assays, even though the culture media of A549 and HEP G2 cells were replaced with WS 2 -loaded serum-free media aer reaching $80% conuence. 57,58 In other words, our current A549 and HEP G2 cell experiments are more similar to Chae and coworkers' experiment on HEK293f as mentioned above. On the contrary, in the antibacterial experiments, the WS 2 nanosheets were kept "naked" during the entire incubation with bacteria.…”
Section: In Vitro Cytotoxicity To Eukaryotic Cellssupporting
confidence: 71%
See 1 more Smart Citation
“…In our current study, WS 2 nanosheets were probably partially coated with protein FBS in the cell viability assays, even though the culture media of A549 and HEP G2 cells were replaced with WS 2 -loaded serum-free media aer reaching $80% conuence. 57,58 In other words, our current A549 and HEP G2 cell experiments are more similar to Chae and coworkers' experiment on HEK293f as mentioned above. On the contrary, in the antibacterial experiments, the WS 2 nanosheets were kept "naked" during the entire incubation with bacteria.…”
Section: In Vitro Cytotoxicity To Eukaryotic Cellssupporting
confidence: 71%
“…While a well-documented mechanism is still absent, a possible reason is proposed to be the existence of nuclear membrane in eukaryotic cells. In addition, as suggested from our previous studies, 57 biomolecules like proteins can rapidly adsorb onto nanomaterial surfaces to form protein corona which can effectively reduce their cytotoxicity. In our current study, WS 2 nanosheets were probably partially coated with protein FBS in the cell viability assays, even though the culture media of A549 and HEP G2 cells were replaced with WS 2 -loaded serum-free media aer reaching $80% conuence.…”
Section: In Vitro Cytotoxicity To Eukaryotic Cellsmentioning
confidence: 99%
“…All together, these observations lead to conclude that, also compared to other carbon nanomaterials, GOs and especially FLG exert very weak cytotoxicity on skin keratinocytes. Even though GBMs cytotoxicity could be reduced by a protein corona due to the presence of serum inside culture medium6768, the present results suggest an acceptable biocompatibility of these materials, both after short acute exposure times (i.e. 24 h) and after long-term exposure to low GBMs concentrations (0.1 μg/mL, up to 10 days).…”
Section: Resultsmentioning
confidence: 58%
“…Similarly, Chong et al [84] also found that adsorption of serum proteins onto GO drastically reduced their cytotoxicity towards A549 lung carcinoma cells and found that GO exhibits a dramatic enhancement of adsorption capacity compared to SWCNTs. In a subsequent study, coating of GO with BSA was suggested to reduce cytotoxicity towards A549 cells by reducing the physical interaction of GO with the cell membrane [85]. It is noted, however, that A549 is a notoriously robust carcinoma cell line not reflective of normal cell physiology.…”
Section: Bio-corona Formation On Carbon-based Nanomaterialsmentioning
confidence: 99%